Human-environment interaction during the Holocene along the shoreline of the Ancient Lake Ladoga: A case study based on palaeoecological and archaeological material from the Karelian Isthmus, Russia - Alenius T; Gerasimov D; Sapelko T; Ludikova A; Kuznetsov D; Golyeva A; Nordqvist K (SAGE PUBLICATIONS LTD, 2022)
This paper presents the results of pollen, diatom, charcoal, and sediment analyses from Lake Bol'shoye Zavetnoye, situated between the Gulf of Finland and Lake Ladoga on the Karelian Isthmus, north-western Russia. The main goal is to contribute to the discussion of Neolithic land use in north-eastern Europe. The article aims to answer questions related to Stone Age hunter-gatherer economy, ecology, and anthropogenic environmental impact through a comprehensive combination of multiple types of palaeoecological data and archaeological material. According to diatom data, Lake Bol'shoye Zavetnoye was influenced by the water level oscillations of Ancient Lake Ladoga during much of the Holocene. Intensified human activity and prolonged human occupation become visible in the Lake Bol'shoye Zavetnoye pollen data between 4480 BC and 3250 BC. During the final centuries of the Stone Age, a new phase of land use began, as several anthropogenic indicators, such asTriticum, Cannabis, andPlantago lanceolataappear in the pollen data and a decrease inPinusvalues is recorded. In general, the results indicate that socio-cultural transformations could have taken place already from the mid-5th millennium BC onwards, including new ways of utilizing the environment, perhaps also in the field of subsistence, even though the livelihood was based on foraging throughout the period.